Riscos e danos relacionados ao contexto do trabalho da equipe de enfermagem de unidades neonatais - Silva, Ana Patrícia Batista (2018)
To analyze the work context and occupational damage, from the perspective of nursing staff professionals, in an Intensive Care Unit and Neonatal Intermediate Unit. METHODS: Cross-sectional, observational study with quantitative-qualitative approach performed at a large public health institution in the state of Goiás. The sample consisted of 44 workers from the neonatal units nursing team. Data collection was performed in the months of July and September of 2017 through observation and interview. For the data analysis, descriptive and analytical statistics were used using Student's t test and ANOVA for associations and Pearson's test for correlations, with a significance level of 5% (p ≤ 0,05). RESULTS: As for the professional profile, eight (18,2%) were nurses, 27 (61,4%) technicians and nine (20,4%) nursing assistants, female (100%), and mean age of 41,7 (± 9,7) years. The work context, from the perspective of the workers, was considered critical. For the organization of work, the items "excessive work rate" and "strong collection by results" presented higher averages (4,2±1,0), classified as severe. Concerning the working conditions, the highest averages corresponded to the "uncomfortable physical environment" (4,0±1,3), "a lot of noise in the environment" (4,1±1,1) and "inadequate physical space" (3,4±1,4). In the socio-professional relations, the highest averages involved "non-existent autonomy" (3,5±1,3) and "disputes among professionals" (3,5±1,1). A significant statistical difference was found between the two units for work organization factors (p=0,048), working conditions (p=0,046) and socio-professional relationships (p=0,0001). Regarding the occupational damage, the critical evaluation prevailed, with the psychological one having the highest mean (3,9±2,0) in the Intensive Care Unit. Already In the Neonatal Intermediate Unit, greater mean was identified for physical damage (2,6±1,4). There was a significant statistical difference between the Intensive and Intermediate Unit Care for the psychological (p=0,0002) and social (p=0,0009) damages. There was an association between the "work organization" domain and wage income variables (p=0,044) and hourly unit load (p=0,009); for "working conditions", the variables employment bond (p=0,016) and wage income (p=0,0001) were statistically significant. As well as for "physical damages" and the variables performed domestic activity (p=0,009), time acting on the unit (p=0,04) and wage income (p=0,02); for "psychological damages" and "social damages", there was an association with the variables working hours (p=0,02) and work shift (p=0,04/0,005). It was found a moderate and significant correlation between: physical damage and work organization (r=0,5721, p=0,0001), psychological damage and working conditions (r=0,5614, p=0,0001), psychological damage and socio-professional relations (r=0,6687, p=0,0001) and high and significant correlation between social and psychological damage (r=0,9072, p=0,0001). CONCLUSION: The work context of the neonatal units presents unfavorable elements and in inadequacy with the health and safety regulations of the worker, predisposing them to physical, psychic and social damage.